META ANALYSIS OF THE INFLUENCE OF THE PROJECT BASED LEARNING (PjBL) MODEL ON PHYSICS LEARNING OUTCOMES IN SENIOR HIGH SCHOLL - Siti Aminah (Universitas Negeri Padang, 2022)
Many studies related to the application of the PjBL model to student learning outcomes have been published in national and international journals. One of the studies that is able to summarize the results of existing studies as a whole is meta-analysis research. Meta-analysis research is quantitative in nature because it uses statistical calculations to summarize all research results which are not possible with other research methods. The data analysis technique used in meta-analysis research is to calculate the effect size of the related research. Based on the results of the study, three research results were obtained, namely the use of the PjBL model on high school physics learning outcomes had an effective influence on learning outcomes of knowledge and skills, class X and XI levels as well as physics subject matter units in high school, namely optical devices, simple harmonic motion, static fluid, dynamic fluid, newton's law, impulse and momentum, straight motion, heat, and work and energy. However, the use of the PjBL model is less effective for dynamic electric matter units, elasticity, and Kepler's law due to certain factors.